High-Speed Near Infrared Optical Receivers Based on Ge Waveguide Photodetectors Integrated in a CMOS Process. (11th May 2008) - Masini, Gianlorenzo; Sahni, Subal; Capellini, Giovanni; Witzens, Jeremy; Gunn, Cary
Abstract : We discuss our approach to monolithic intergration of Ge photodectors with CMOS electronics for high-speed optical transceivers. Receivers based on Ge waveguide photodetectors achieve a sensitivity of− 14.2 dBm (10 − 12  bit error rate (BER)) at 10 Gbps and 1550 nm.